Knowledge Management for Educational Information Systems - Thorn, Christopher A. (Education Policy Analysis Archives, 2001)
This article explores the application of Knowledge Management (KM) techniques to educational information systems—particularly in support of systemic reform efforts. The first section defines knowledge and its relationship to information and data. There is also a discussion of various goals that might be pursued by organizations using KM techniques. The second section explores some of the fundamental design elements of an educational KM system. These include questions surrounding the unit of analysis, distributed computer resources, and organizational characteristics of successful KM efforts. Section three outlines the benefits that organizations expect to gain by investing in KM. Section four is a case history of the introduction of a district-level data system and the parallel efforts to support the aggregation and reporting of high-stakes educational outcomes for 8th grade students in the Milwaukee Public Schools (MPS) district. Finally, there are some preliminary conclusions about the capacity of an urban district in a complex policy environment to respond to the knowledge management needs of a decentralized system.